Universal Amplification-Free RNA Detection by Integrating CRISPR-Cas10 with Aptameric Graphene Field-Effect Transistor - Sun, Mingyuan; Yu, Zhenxiao; Wang, Shuai; Qiu, Jiaoyan; Huang, Yuzhen; Chen, Xiaoshuang; Zhang, Yunhong; Wang, Chao; Zhang, Xue; Liang, Yanbo; Liu, Hong; She, Qunxin; et al. (Nano-Micro Letters, 2025)
Amplification-free, highly sensitive, and specific nucleic acid detection is crucial for health monitoring and diagnosis. The type III CRISPR-Cas10 system, which provides viral immunity through CRISPR-associated protein effectors, enables a new amplification-free nucleic acid diagnostic tool. In this study, we develop a CRISPR-graphene field-effect transistors (GFETs) biosensor by combining the type III CRISPR-Cas10 system with GFETs for direct nucleic acid detection. This biosensor exploits the target RNA-activated continuous ssDNA cleavage activity of the dCsm3 CRISPR-Cas10 effector and the high charge density of a hairpin DNA reporter on the GFET channel to achieve label-free, amplification-free, highly sensitive, and specific RNA detection. The CRISPR-GFET biosensor exhibits excellent performance in detecting medium-length RNAs and miRNAs, with detection limits at the aM level and a broad linear range of 10−15 to 10−11 M for RNAs and 10−15 to 10−9 M for miRNAs. It shows high sensitivity in throat swabs and serum samples, distinguishing between healthy individuals (N = 5) and breast cancer patients (N = 6) without the need for extraction, purification, or amplification. This platform mitigates risks associated with nucleic acid amplification and cross-contamination, making it a versatile and scalable diagnostic tool for molecular diagnostics in human health. Highlights: 1 A collaborative biosensing system is developed for amplification-free RNA/miRNA detection by integrating Type III CRISPR-Cas10 system with a graphene field-effect transistor (GFET). 2 Continuous cleavage of ssDNA by the mutant CRISPR-Cas10 effector complexes and high charge density of hairpin DNA reporters on the GFET channel enable the detection limit to reach the level of aM. 3 A universal sensing detection platform is established to directly detect the medium-length RNAs and miRNAs in clinical samples with the recognition capability of single nucleic acid.